Topographical investigation and magnetometer prospection of the Agighiol tumulus, Tulcea County (4th century BC) - Zickgraf, B.; Riese, T.; Teleaga, E. (Materiale și Cercetări Arheologice)
The Agighiol tumulus was investigated in 1931 after the unprofessional dismantling of the funerary construction. The rediscovery of the documentation of the archaeological excavation has allowed the revalorization of this monument, finding that only a quarter of the tumulus had been investigated. In order to estimate the potential of further systematic archaeological excavation, a detailed topographical survey of the mound and a magnetometer prospection of its surface were carried out. The topographic elevation revealed a depression with raised edges corresponding to the pit of the old excavations. The geomagnetic prospection aimed at the discovery of possible funerary structures; the remains of the funerary structure had a circular form; possible anthropogenic pits were also identified near the mound.